IMPLEMENTATION OF ENTREPRENEURSHIP-BASED GOVERNMENT IN THE LOCAL GOVERNMENT: CASE STUDY IN KEBUMEN, INDONESIA - Prasetyo, Hendrawan (Natapraja, 2022)
Being an adaptive and responsive bureaucratic apparatus in serving the community is something that absolutely must be done. A proactive attitude towards the progress and development of community life must also be possessed by the bureaucratic apparatus as a public servant. Therefore, the bureaucratic apparatus is required to have an entrepreneurial spirit (entrepreneurial bureaucracy). This study aims to find out how to entrepreneurship the local government bureaucracy in Kebumen Regency and to find out how the implementation of entrepreneurship in the bureaucracy is as a transformation of the entrepreneurial spirit in the public sector, as well as what are the problems faced in entrepreneurship bureaucracy in the Kebumen Regency Government. This study uses a qualitative approach, which is trying to get as complete information as possible about how to apply entrepreneurial principles to the bureaucracy through in-depth interviews. The writing is focused on issues related to the transformation of entrepreneurship in the bureaucracy in the local government of Kebumen Regency. The research subjects were the researchers themselves, while the informants used to collect data through interviews consisted of elements of the local government of Kebumen Regency. Based on the results of the research conducted, the concept of entrepreneurship of the Kebumen Regency Government bureaucracy through the principles of bureaucratic entrepreneurship has been carried out by various public service agencies. The principle of bureaucratic entrepreneurship is characterized by several things, namely: professional, innovative, effectiveness, efficiency, productivity and customer oriented.Keywords: adaptive, entrepreneurial bureaucracy, good corporate governance, responsive